THE TRANSFORMATION OF PEKEN KLANGENAN KOTAGEDE INTO A SUSTAINABLE CULTURAL TOURISM DESTINATION: A COLLECTIVE NARRATIVE ANALYSIS OF MANAGERS, TENANTS, AND TOURISTS (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
This study aims to identify the construction of the meaning of sustainability among actors and to provide a comprehensive understanding of how Peken Klangenan Kotagede can be positioned as a model of sustainable cultural tourism. This study employs a qualitative ethnographic method. The sampling technique combines purposive, snowball, and convenience sampling. Informants consist of managers, tenants, and tourists. Data collection was conducted through in-depth interviews, observation, and documentation. Data validity was ensured using triangulation of sources, techniques, and time. Data analysis follows Miles and Huberman’s framework, incorporating thematic, narrative, and phenomenological approaches. The findings indicate that Peken Klangenan Kotagede can be positioned as a model of sustainable cultural tourism by involving managers, tenants, tourists, and the community. Sustainable tourism in Peken Klangenan is already linked to economic, socio-cultural, and environmental aspects. Peken Klangenan Kotagede functions as a socio-cultural laboratory, a place where sustainability, cultural tourism, and transformation converge, creating a destination that is not only for tourism consumption but also a space for learning, preservation, and community empowerment.
Keywords: Sustainable tourism; cultural tourism; transformation; Peken Klangenan Kotagede